2011
DOI: 10.1097/id.0b013e3182386d74
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of Graft Materials Using Autogenous Teeth in Maxillary Sinus Augmentation

Abstract: The results indicated that autogenous tooth bone graft materials are appropriate for use in maxillary sinus augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 16 publications
4
57
0
2
Order By: Relevance
“…Among them, the emerging autogenous dentin materials were successfully used for various clinical situations including guided bone regeneration (GBR), sinus grafts, and ridge preservation [20,21]. Many studies have indicated that manipulated dentin materials can act as osteoconductive or even osteoinductive substitutes for common graft biomaterials [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the emerging autogenous dentin materials were successfully used for various clinical situations including guided bone regeneration (GBR), sinus grafts, and ridge preservation [20,21]. Many studies have indicated that manipulated dentin materials can act as osteoconductive or even osteoinductive substitutes for common graft biomaterials [31].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have demonstrated that DDM is well-tolerated when used to fill the ridge defects, indicating promising potential for bone regeneration [13][14][15]20]. Similarly, the effectiveness of DDM as a bone substitute has already been identified in various clinical circumstances such as the alveolar bone regeneration associated with dental implants, sinus augmentation, and preservation of extraction sockets [13][14][15]21,22]. In these studies, DDM completely fulfills the criteria for a bone regeneration material, possessing osteoinductive and osteoconductive properties [23].…”
Section: Introductionmentioning
confidence: 99%
“…The analyses of mandibular cortical bone taken from patients, crown of autogenous tooth bone graft material, root of autogenous tooth bone graft material, irradiated mineralized allogeneic cancellous bone (ICB; Rocky Mountain Tissue Bank, Denver, CO, USA), xenograft bone (Bio-Oss), and synthetic bone MBCP (Biomatlante, Vigneux de Bretagne, France) showed that the x-ray diffraction (XRD) pattern of dentin of autogenous tooth bone graft material and allograft bone was most similar to autogenous bone, and this finding has been announced 50 . Many authors have published case reports as well as the results of clinical studies on sinus bone graft, ridge augmentation, guided bone regeneration, socket preservation or graft, and they have proven to be useful materials for hard tissue defect restoration [51][52][53][54][55][56][57][58][59] . Lee 60 performed quantitative analysis of the proliferation and differentiation of the MG-63 cell line on the bone grafting material using human tooth.…”
Section: Discussionmentioning
confidence: 99%
“…These constituents, especially type I collagen, are very similar to those in dentin and alveolar bone. Previous studies on AutoBT demonstrated active bone formation and remodeling through osteoconduction and osteoinduction, with little or no infection risk despite the partially opened wound after surgery 4,5,10,11) . More importantly, since AutoBT was fabricated by bio-recycling the patient's own extracted tooth, it is less technique-sensitive and is patient-friendly without any major surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The organic and inorganic contents in AutoBT are very similar to those in alveolar bone. Moreover, AutoBT possesses the same capabilities as the autogenous bone graft since it showed osteoconduction, osteoinduction, and bone remodeling 4,5) . This article reports five cases of the successful use of chin bone graft and AutoBT in alveolar cleft repair.…”
Section: Introductionmentioning
confidence: 99%